(untitled) - Wolfram, Stephen (Reading, Mass, 1992)
Contents: Tour of mathematica; mathematica graphics gallery; principles of mathematica; advanced mathematics in mathematica.
Keywords: Mathematics; Toán học,Data processing; Xử lý dữ liệu